Mechanisms of increasing predation by planktivorous fish with rising temperature may explain the temperature–body size relationships in zooplankton - Maszczyk, Piotr; Wilczynski, Wojciech; Gliwicz, Z. Maciej; Leniowski, Konrad; Zebrowski, Marcin Lukasz; Lee, Jae-Seong; Babkiewicz, Ewa (Frontiers in Ecology and Evolution, 2023)
The temperature-size rule (TSR) has been consistently observed in numerous studies, showing that ectotherms reared at higher temperatures experience accelerated growth during the juvenile stage and ultimately reach smaller sizes and younger ages at maturity. One explanation for this response is that it occurs when the effect of temperature on mortality, including predation, outweighs its effect on food intake and metabolism. While several studies have found that the latter effect is close to the expected result based on the Q10=2 assumption, confirmation of this hypothesis requires evidence that the effect of temperature on mortality exceeds the Q10=2 threshold. To test this hypothesis, we conducted experiments with two fish species: rudd and Malabar danio. We examined the capture rate, which serves as a proxy for mortality, as well as the standard metabolic rate (SMR) and several parameters characterising the mobility of the fish and their planktonic prey (Daphnia) at different temperatures. The results strongly supported our hypothesis, as the capture rate increased significantly more than expected based on the Q10=2 assumption, especially for the danio. This substantial effect cannot be attributed solely to the thermal sensitivity of the SMR, as the Q10 for the SMR was only around 2. The most likely explanation seems to be a much more pronounced increase in the fish's mobility and resulting reaction field volume compared to its planktonic prey at elevated temperatures. This increased mobility leads to an improved attack rate by the fish, which exceeds the prediction made by the Q10=2 assumption. This mechanism may explain not only the TSR pattern in zooplankton, but also their reduced mean body size and density at population and community levels at elevated temperatures, and may hypothetically be observed at other predator-prey interfaces.